Lymfatické mapování u karcinomu cípku dĕlozního - Sevcík, L; Klát, J; Gráf, P; Curík, R; Kraft, O; Jalůvková, Z (Klinicka onkologie, 2008)
BACKGROUND AND AIMS: The aim of the study is to analyze the feasibility of intraoperative sentinel lymph nodes (SLN) detection using gamma detection probe and blue dye in patients with cervical cancer. DESIGN AND SUBJECTS: Prospective clinical study. 106 patients with cervical cancer were included into the study in the period from May 2004 to November 2006. METHODS AND RESULTS: Patients were divided into three groups according to the tumor volume. Lymphoscintigraphy was performed following an injection of 99m Tc-labeled nanocolloid and intraoperatively the SLN were identified visually after marking of lymphatic vessels with blue dye and further detected using a handheld gamma detection probe. The SLN were histologically and immunohistochemically analyzed. Total number of 309 SLN with an average of 2.9 per patient were identified. The SLN detection rate was 94.3% per patient, 84.4 % per side, and depended on the tumor volume. Metastatic disease was detected in 39 patients (36.8%) and micrometastatic disease in 15 patients (14.2%). Sensitivity and negative predictive value calculated were 93.9% and 98.0%, false negative rate reached 5.1. CONCLUSIONS: Intraoperative detection of SLN using combination of technecium-99-labeled nanocolloid and blue dye represents a feasible, safe and accurate technique to identify lymphatic spreading in stages IA2-IB1 of cervical cancer.
Keywords: senioři; technecium 99mTc-agregovaný albumin; senioři nad 80 let; Radiopharmaceuticals; radiofarmaka; Sentinel Lymph Node Biopsy; Middle Aged; lymfatické metastázy; Sensitivity and Specificity; Adult; nádory děložního čípku; Lymphatic Metastasis; Aged, 80 and over; Technetium Tc 99m Aggregated Albumin; ženské pohlaví; Humans; lidé středního věku; barvicí látky; senzitivita a specificita; Uterine Cervical Neoplasms; dospělí; biopsie sentinelové lymfatické uzliny; Aged; Female; Coloring Agents; lidé